Knowledge and perception on Oral Hygiene Instructions and Periodontal Health Education (OHIPE) among UiTM dental undergraduates / M.A. Abd Halim ... [et al.] - M.A., Abd Halim; H., Hazudin; M., Masud; F., Ariffin (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
This study was aimed to evaluate the knowledge and perception of oral hygiene instructions and periodontal health education (OHIPE) among dental undergraduates of Universiti Teknologi MARA (UiTM) after the modification of OHIPE protocol. This cross-sectional study was carried out among 134 clinical dental year students of UiTM. The data was collected by distributing a self-administered structured questionnaire to the participants. The questionnaire was divided into two different sections in order to assess knowledge and perception independently. The 5-point Likert Scale was used to evaluate perception. Data analysis was done via SPSS version 27.0. Results: There was 51.3% (n=40) year 5 students obtained good knowledge score compared to only 21.4%(n=12) of year 4 students. The remaining 48.7%(n=38) of year 5 and 71.4%(n=40) year 4 students recorded average knowledge (P <0.001). Students' perception regarding OHIPE showed that the response on each of the six questions were almost similar. However, there were statistically significant differences between the two groups regarding giving information about patient's periodontal status and advice on cleaning interdental areas of the teeth (P = 0.01 - 0.031). Most students agreed that usage of patient's own periodontal chart and radiograph is important and useful during OHIPE. Conclusion: Periodontal health care knowledge score for OHIPE among clinical years students are between average and good. The knowledge and awareness of year 4 students were lower than year 5 students which could be due to reduced clinical sessions during pandemic of Covid-19. Perception of students were similar among all participants as they have more clinical experience in managing periodontal patients.